LCA Water Footprint AWARE Characterization Factor Based on Local Specific Conditions - Ansorge, Libor; Beránková, Tereza (European Journal of Sustainable Development, 2017)
A Water Footprint based on Life Cycle Assessment (LCA) methodology is a modern approach to the assessment of impacts of water use on the environment. The Available WAter REmaining (AWARE) method is the recommended characterization method by the WULCA Working group to perform a water consumption impact assessment in LCA. The published values of AWARE characterization factor were computed using the hydrological model at the country and main river basin levels only. These “average” values can be imported into the LCA software and used for LCA studies. The scale of available AWARE data could be insufficient for studies at a local level due to heterogeneous conditions in various countries or large river basins. In our study, we use runoff data from the Europe region available in the Global Runoff Data Centre for computation of “regionalized” AWARE values and compare them with AWARE values at the country and river basin levels. The analysis of computed values indicates that the variance of AWARE values can be very large in some countries and river basins. Keywords: Water footprint – life cycle assessment – characterization factor – hydrological conditions